Mechanical Properties and Biocompatibility of 3D Printing Acrylic Material with Bioactive Components - Raszewski, Zbigniew; Chojnacka, Katarzyna; Kulbacka, Julita; Mikulewicz, Marcin (Journal of functional biomaterials, 2022)
UNLABELLED: The aim of this study was to create a 3D printing material with bioactive properties that potentially could be used for a transparent removable orthodontic appliance. MATERIALS AND METHODS: To acrylic monomers, four bioactive glasses at 10% concentration were added, which release Ca, P, Si and F ions. The materials were printed on a 3D printer and tested for flexural strength (24 h and 30 days), sorption and solubility (7 days), ion release to artificial saliva pH = 4 and 7 (42 days) and cytotoxicity in the human fibroblast model. The released ions were determined by plasma spectrometry (Ca, P and Si ions) and ion-selective electrode (F measurement)s. RESULTS: The material obtained released Ca2+ and PO43- ions for a period of 42 days when using glass Biomin C at pH 4. The flexural strength depended on the direction in which the sample was printed relative to the 3D printer platform. Vertically printed samples had a resistance greater than 20%. The 10% Biomin C samples post-cured for 30 min with light had a survival rate of the cells after 72 h of 85%. CONCLUSIONS: Material for 3D printing with bioactive glass in its composition, which releases ions, can be used in the production of orthodontic aligners.
Keywords: bioactive glass; ion release; 3D printing; mechanical properties